Hymnic allusions in the exordium of the Argonau-tica of Apollonius of Rhodes: Renewed traditions and traditional innovations (Circe de clásicos y modernos, 2017)
In the exordium of the Argonautica, Apollonius makes a series of hymnic allusions that gives his poem a greater depth of meaning and a different literary texture. In this work we will analyze how, from a series of allusions to the exordium of the Phaenomena of Aratus, Apollonius introduces elements of the hymnic repertoire in his epic, and how he fuses the epic invocation to the Muses with the hymnic prayer and what are the meanings and functions of this fusion.
Keywords: allusion; Argonautica; Epic; Homer; Hymn